Exploring the Dynamic Relationship Between Stock Market Indices and Exchange Rates: During and After the Crises—Insights from G20 and Asian Countries - Saijai, Worrawat; Pankwaen, Kansuda; Thongkairat, Sukrit (SOUTHEAST ASIAN JOURNAL OF ECONOMICS, 2025)
The global financial landscape has been profoundly affected by crises such as the COVID-19 pandemic, the Russia-Ukraine war, and geopolitical trade disputes, leading to heightened volatility in stock and foreign exchange markets. This study examines the dynamic spillovers between stock indices and exchange rates across G20 countries and key Asian economies, including Thailand and China, from January 2012 to June 2023. Employing the DCCGJR-GARCH(1,1) model with one-step estimation, which efficiently captures time-varying correlations in high-dimensional datasets, the study provides a comprehensive analysis of crisis-induced market fluctuations. Findings reveal significant shifts in correlation structures, volatility persistence, and spillover effects, particularly during major crises, emphasizing the role of economic uncertainty indicators such as the VIX. These insights are critical for policymakers, investors, and financial analysts, offering a deeper understanding of risk transmission and aiding in strategic decision-making for market stability, portfolio diversification, and crisis preparedness.